POSISI STRATEGIS DAN STRATEGI PERTUMBUHAN PT AKR CORPORINDO TBK: PENDEKATAN MANAJEMEN STRATEGIS TERINTEGRASI - Sahidna, Ana (Politeknik Ubaya, 2026)
This study aims to analyze the strategic positioning and determine the most appropriate growth strategy for PT AKR Corporindo Tbk using an integrated strategic management approach. The research applies a qualitative descriptive method with a case study design and utilizes secondary data obtained from the company’s 2024 annual report and supporting documents. The analytical framework follows three stages: input stage, matching stage, and decision stage. In the input stage, the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices are used to assess the company’s strengths, weaknesses, opportunities, and threats. The findings indicate that the company possesses strong internal capabilities and favorable external conditions. In the matching stage, the IE Matrix positions the company in Quadrant I (grow and build), suggesting that aggressive growth strategies are appropriate. The alternative growth strategies formulated and researched include market penetration, market development, product development, and forward integration. Alternative strategies are subsequently evaluated using the Quantitative Strategic Planning Matrix (QSPM). The results reveal that market penetration achieves the highest Total Attractiveness Score compared to other strategic options. This strategy is considered the most relevant because it enables optimization of existing distribution assets and increases sales volume within current markets. Supported by integrated logistics infrastructure and digital transformation, the market penetration strategy is expected to promote sustainable growth and strengthen the company’s competitive position in the national energy and logistics industry.